The Influence of the Problem Posing Learning Model on Students' Mathematical Problem Solving Abilities in One-Variable Linear Materials - Pamungkas, Magita Danang; Ali, Mohamad Bilal (Prodi Tadris Matematika Fakultas Tadris Umum, 2024)
The primary objective of this study is to investigate the impact of the problem posing learning model on the mathematical problem solving abilities of seventh-grade students in the topic of one-variable linear equations. The study aims to determine the extent to which the problem posing learning model influences students' mathematical problem solving abilities at SMPN 2 Gading. Additionally, the study seeks to examine the students' learning activities during the implementation of the problem posing learning model in the context of one-variable linear equations, and to evaluate the effectiveness of implementing the problem posing learning model for seventh-grade students at SMPN 2 Gading. The sampling technique employed in this study is purposive sampling with a simple random sampling approach. The data collection involves essay questions comprising three items to assess students' mathematical problem solving abilities. These questions were pre-tested for validity, reliability, distinguishing power, and level of difficulty. The findings of the research indicate a significant influence of the problem posing learning model on the mathematical problem solving abilities of seventh-grade students at SMPN 2 Gading. The effect size value is reported to be 4.202, indicating a substantial impact. Moreover, the study observes a change in student activities during the learning process, with an increase in student engagement, particularly during the second meeting. The implementation of the problem posing learning model for seventh-grade students at SMPN 2 Gading is reported to have proceeded smoothly from the first to the last meeting.